A novel antibacterial zirconia-containing PMMA bone cement. (May 2022) - Chen, Yong; Caneli, Gulsah; Almousa, Rashed; Xie, Dong
Abstract: A non-leaching antibacterial bone cement has been developed and evaluated. Chlorine- and bromine-containing furanone derivatives were synthesized and covalently coated onto the surface of zirconia filler particles, followed by mixing into a conventional poly(methyl methacrylate) bone cement. Flexural strength and bacterial viability were used to evaluate the modified cements. Effects of coated antibacterial moiety content, coated zirconia loading and halogen on furanone were investigated. Results showed that the experimental cement showed significant enhanced antibacterial function against bone-associated Gram-positive Staphylococcus aureus as well as Gram-negative Pseudomonas aeruginosa, as compared to commercial PMMA cement. The cement also exhibited a comparable flexural strength to and 3–14% higher flexural modulus than commercial PMMA bone cement. Increasing antibacterial moiety content and filler loading significantly enhanced antibacterial activity. Increasing antibacterial moiety content slightly increased both flexural strength and modulus of the modified cement. Increasing filler loading slightly increased flexural strength up to 7% loading and then decreased. The bromine-containing furanone modified cement showed a higher antibacterial activity than its chlorine counterpart. Antibacterial agent leaching tests exhibited that the modified experimental cement showed no leachable antibacterial components to surroundings. Within the limitations of this study, this experimental poly(methyl methacrylate) cement may find potential applications in orthopedics for reducing in-surgical and post-surgical infection after further investigations are conducted.